Data Economy and Antitrust Regulation - Christian Rusche (Intereconomics, 2019)
Data becomes a more and more important factor in the economy. To fully develop the economic potential of the data economy, antitrust regulation has to prevent the abuse of market power while sustaining the benefits of cooperation. This paper presents the pillars of European antitrust regulation and explains the particular challenges posed by data. Finally, it is shown that current antitrust law is well prepared to meet these requirements.
Keywords: 330